Wounds and mental health care: system thinking. Issue 4 (28th November 2019) - Samuriwo, Ray; Hannigan, Ben
Abstract : Purpose: This paper considers how the quality of wound care delivered to people experiencing mental ill health can be improved at the system level in line with the global focus on improving population health. The purpose of this paper is to identify how the quality of wound care delivered to mental health care service users can be improved at a population level through system thinking informed by boundary theory. Design/methodology/approach: This paper is a critical analysis of practice underpinned by systems thinking and boundary theory. Findings: Tissue viability care and mental health care have different professional cultures and identities that are manifest in the way that they are organised and deliver care. If improvements in wound care-related outcomes at a population level are to be achieved, then it is important that the wound care needs of people experiencing mental ill health are addressed. Systems thinking and boundary theory provide a useful conceptual framework for informing quality improvement for people experiencing mental ill health at a population level. Integrated care plans are a useful mechanism for delivering comprehensive care that brings about wound healing and recovery from mental ill health. Social implications: Integrated wound and mental health care plans transcend the professional boundaries that exist between tissue viability and mental health care services. Improvements in the quality and safety of care delivered to people with wounds who also utilise mental health services can be achieved through the use of integrated care plans. Health care policy and organisation need to meet the wound-related needs of people using mental health services. Originality/value: There has been a focus on improving many aspects of wound care in line with the global focus on grand convergence in population health, but there has been very little emphasis on improving the wound-related outcomes of people that use mental health services. Systems thinking and boundary theory provide a useful framework for understanding how wound care for people experiencing mental ill health can be improved at a population level. Integrated care plans are a useful way of ensuring that safe high-quality wound care is consistently delivered to people experiencing mental ill health.